Individual response of hematologic parameters after altitude exposure in endurance athletes - Lippi, G.; Salvagno, G. L. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
The enhancement of the red blood cells mass in athletes has several advantages, optimizing blood`s oxygen carrying capacity and improving athletic performances, especially in endurance sports. Altitude training is a procedure frequently used by competitive athletes to improve sea-level performance. At higher altitudes, the relative oxygen content of the air is reduced. Therefore, after an adequate period of exposure, the body "acclimates" and responds with a complex series of biological and metabolic adaptations, though definitive and objective benefits are as yet to be determined. Acclimatization to high altitude results in a wide series of central and peripheral adaptations that comprehend increase in (I) red blood cell mass and hematocrit, (II) total blood and capillary volume, (III) volume of mitochondria, (IV) efficiency of gas exchange, (V) VO2 max and aerobic capacity, (VI) faster muscle recovery and ultimately improve oxygen delivery and utilization. In synthesis, endurance exercise training at altitude or in hypoxic conditions induce several physiological adaptations, and several studies have demonstrated the cardiovascular or ventilatory benefits following altitude training or acclimatization to hypoxia. Several different approaches were proposed to optimize the acclimatization changes: live high and train high (5), live high and train low and intermittent exposure. Aggregated results of current literature indicate that continuous living and training at moderate altitude does not improve sea level performance of high level athletes. Therefore, acclimatization to moderate high altitude, accompanied by training at low altitude (the so-called "living high-training low" theory), is likely the most effective variant of the altitude training to improve sea level endurance performances. Despite promising results, some later investigations described a wide interindividual variability in adaptive response and athletic performance after a traditional altitude training camp, allowing the clustering of athletes between subjects who responded to altitude training and those who were "nonresponders". It has been postulated that such an individual variability may be accounted for by two mechanistic pathways: altitude-acclimatization response and training effects. The reason for such a variable hematological response is yet unclear, but is likely multifactorial, and includes heterogeneity in hypoxic ventilatory drive, O2 half-saturation pressure of hemoglobin, hypoxia-induced transcriptional regulation of Epo synthesis and production, Epo metabolism, and sensitivity of the bone marrow stem cells to Epo and other growth factors. A further intriguing issue is the balance between effectiveness and risks of iron supplementation therapy in athletes. Iron supplementation therapy is commonplace in athletes to counterbalance physiological or pathological anemia and to prevent physiologic dysfunction; however, its misuse might occasionally result in iron overload, which is not free from several metabolic risks. The present investigation aims to identify the major metabolic and hematologic adaptations to altitude training in elite endurance athletes (professional cross-country skiers), considering also the balance between beneficial effects and virtual complications of different typologies of endurance hypoxic training in these peculiar subset of competitive athletes.